Rehabilitation Measures Planning based on the Analysis of Functional Impairments and Disabilities due to Chronic Kidney Disease: a Retrospective Study - Zhanna M. Kalacheva; Natalia S. Zapariy; Denis D. Bolotov; Magomed A. Omarov; Konstantin A. Sarkisov (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. Quality of functional impairments analysis and the degree of disability associated with chronic kidney disease is a keyfactor of the effectiveness of the rehabilitation measures organization for persons with disabilities with the above pathology.AIM. To assess the degree of physical dysfunction of the disabled persons due to the chronic kidney disease on the basis of the clinicaland functional disorders to determine the need for rehabilitation measures.MATERIAL AND METHODS. The study was generated in the form of the Excel spreadsheet using the following methods: documentary,excerpting data in the volume of 265 units. For quantitative variables, statistical indicators were used: mean and median. To comparetwo independent groups, the reliability index was used, the X2 statistic and Spearman's rank correlation coefficient were performed. Thesignificance level for testing statistical hypotheses was assumed to be 0.05. Processing and analysis was performed in the R environment(environment for statistical data analysis. http://www-r-project.org).RESULTS AND DISCUSSION. In these patients, the largest proportion in the structure of physical dysfunctions were limitations toself-care, first-degree movement, labor activity and second-degree self-care, and third-degree labor activity. Analysis of the degreeof severity of disability depending on the stage of the disease, which determines the structure of social insufficiency and reducedquality of life, can be accepted as a basis for planning rehabilitation measures. At the same time, due to the predominance of generalsymptomatology, analysis of clinical signs of chronic kidney disease, taking into account the stage of the disease, can be recognizedonly as an auxiliary mechanism.CONLUSION. Expert-rehabilitation diagnostics among persons who have undergone primary and repeated examination allows us toget an idea of the rehabilitation measures amount required for them, taking into account the stage of the process in certain subgroups.When forming an individual rehabilitation program, the use of ICF is indispensable.